Motivational and emotional states in self-directed language learning: a longitudinal study - Samane Chamani; Atefeh Razi; Ismail Xodabande (Springer, 2023)
Abstract The current longitudinal case study investigated emotional and motivational states in a self-directed and mobile-assisted language learning environment. The participant of the study was a highly motivated language learner who used the Busuu application for a period of one year to learn German. Tracing the participant's emotional and motivational journey using solicited diaries and chat-based interviews, the study revealed that the process of self-directed language learning is associated with the experience of a variety of positive and negative emotions. Joy, hope, and interest were the prevailing positive emotions that were linked to learning vocabulary; and frustration, anger, and feeling annoyed were the negative emotions in relation to learning grammar and pronunciation. In general, the study found a strong connection between positive emotions and persistence in self-directed language learning. The findings also pointed to some possible causes of high dropouts in application based language learning, as lack of enough resources for learning some language skills (such as grammar) initiated and implicated extensive processes of negative emotions. The study contributes to the growing body of knowledge in mobile-assisted language learning, and calls for further research regarding the role of emotions in technology-based and self-directed learning environments.